2009
DOI: 10.1021/ac9007978
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Solid-Phase Microextraction—A New Concept of Sorbent Preparation

Abstract: A new sorption system for isolation/enrichment of polar organic analytes from aqueous samples was obtained by substantial modification of the solid-phase microextraction (SPME) probe. In this system, polar sorbents are separated from the sample by a hydrophobic membrane. The new membrane SPME (M-SPME) probe was made utilizing polyethylene glycol (PEG) (molecular weight = 20 kDa) and polydimethylsiloxane (PDMS) as the membrane material. In this probe, PEG behaves as a pseudo-liquid at the extraction stage, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…For the fiber prepared with direct coating method, the extraction efficiency of the coating is determined by the properties of the analytes and the used sorbent. Using a hydrophobic polymer membrane to separate sorbent and sample was proved to be an effective method to protect polar sorbent [44], but our experimental results showed that the extraction efficiency of the sorbent might be decreased.…”
Section: Resultsmentioning
confidence: 82%
“…For the fiber prepared with direct coating method, the extraction efficiency of the coating is determined by the properties of the analytes and the used sorbent. Using a hydrophobic polymer membrane to separate sorbent and sample was proved to be an effective method to protect polar sorbent [44], but our experimental results showed that the extraction efficiency of the sorbent might be decreased.…”
Section: Resultsmentioning
confidence: 82%
“…The equilibrium time for low concentration ibuprofen was somewhat longer than that for high concentration. According to Fick’s law, the diffusion of low concentration of analytes across the ZIF-8 membrane slowed down47. Moreover, the adsorption capacity significantly increased as the initial concentration of ibuprofen increased, indicating the favorable adsorption at high concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…high density polymers which resemble viscous fluid are used as an extrahent in this two-phase sorption system. The analytes are retained on the fiber via dissolution in the extraction medium [10], [11].…”
Section: Novel Solutions In the Field Of Solid-phase Microextractmentioning
confidence: 99%